Is tobacco smoking protective for sarcoidosis? A case-control study from North India - Gupta, D.; Singh, A.D.; Agarwal, et al., R. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background:While tobacco smoking is commonly believed to be negatively associated with the occurrence of sarcoidosis, the relationship of environmental tobacco smoke (ETS) exposure with sarcoidosis is largely un-explored.We studied the impact of active smoking and ETS exposure on disease severity in newly diagnosed cases of sarcoidosis from India. Methods: Data on demographic variables, smoking habits and exposure to environmental tobacco smoke (ETS) among non-smoker sarcoidosis patients was collected prospectively. Presence of smoking and ETS exposure were compared among cases and controls. Among the sarcoidosis patients, clinical manifestations, radiology, spirometry and histopathological grading of lung biopsy were compared between the smokers vs. non-smokers and ETS exposed vs. not-exposed. Results:We studied 98 newly diagnosed cases of sarcoidosis and 196 age, sex and religion- matched healthy volunteers. The study group comprised of 62 (63%) men and 36 (37%) women.The prevalence of smoking was similar in cases and controls (12.2% vs. 15.3%, p = 0.48). Among the never smoker patients with sarcoidosis, 20 (23%) reported ETS exposure vis-a-vis 57 (34%) in the matched controls. A conditional logistic regression analyses showed insignificant negative association with active smoking (OR 0.75; 95% CI, 0.35-1.56) or ETS exposure (OR 0.58; 95% CI, 0.32-1.06) after adjusting for age, gender, religion, and education.There were no differences in the clinical manifestations, radiological staging, spirometry and histopathological grading of lung biopsy in any of the group comparisons studied. Conclusion: Smoking or ETS exposure may not have significant negative association with sarcoidosis. Also, tobacco smoke might not have any effect on the clinical behavior or disease severity in sarcoidosis. The belief that smoking is protective for sarcoidosis is not substantiated in this study and appears to be misfounded.